Soft Tissue Sarcoma of the Groin: Diagnosis, Management and Prognosis - Brooks, A. D. (Institutional Knowledge at Singapore Management University, 2001)
Soft tissue sarcomas (STS) of the groin may present a difficult problem because of misdiagnosis as groin hernia and proximity to major neurovascular structures. We evaluated our management and survival in a large cohort of patients. STUDY DESIGN: Patients treated between July 1, 1982 and July 1, 1998 with primary or recurrent STS of the groin were included. Groin sarcomas were defined as those tumors within 5 cm of the inguinal crease. Patient, tumor, clinical, and survival data were analyzed using a log rank test and Cox regression. RESULTS: We treated and followed 88 patients with STS of the groin. The median age was 52 years (range 16 to 86 years) and 55 patients (63%) were male. Disease specific survival was 72% at 5 years. Tumors tended to be larger than 5 cm (52%), deep (72%), and high-grade (60%). Unfavorable prognostic factors for disease-specific survival were high grade (p < 0.001), neurovascular invasion (p < 0.001), positive margin (p < 0.01), deep depth (p < 0.01), and selection for adjuvant therapy (p < 0.005). Multivariate analysis indicated age greater than 50 years (p < 0.05), high grade (p < 0.001), neurovascular invasion (p < 0.001), and positive microscopic margins (p < 0.001). Fourteen patients (16%) were diagnosed with STS at hernia operation then went on to a definitive operation with no impact on survival. Seventeen patients (19%) had involvement of a major vessel or nerve, and 5 of these ultimately required amputations, 3 for local recurrence. CONCLUSIONS: High grade, neurovascular invasion, and positive microscopic margins are associated with poor outcomes. The biology of these tumors is similar to other extremity STS, and similar principles of management apply. Even with neurovascular involvement, most patients with primary groin STS do not require amputation.